Influence of proteinuria on the lipoprotein (a) metabolism disorder - Petrović Dejan; Obrenović Radmila; Stojimirović Biljana (Vojnosanitetski Pregled)
Background/Aim. Proteinuria causes lipid metabolism abnormalities. The aim of the present study was to examine the influence of proteinuria on the lipoprotein (a) metabolism disorder. Methods. The study included 60 patients of the male-famele ratio (M : F = 32 : 28), mean age 37.15±9.85 years with, the average endogenous creatinine clearance 86.27±19.81 ml/min, and the average body mass index (BMI) 24.18±2.23 kg/m2. Regarding the level of glomerular proteinuria, the patients were divided into four groups. The first (control) group, with proteinuria levels less than 0.25 g/24h, included 15 patients (M : F = 6 : 9), mean age 34.66±4.82 years, the mean clearance of endogenous creatinine 99.70±12.94 ml/min, and mean BMI 23.28±3.50 kg/m2. The second group, with proteinuria between 0.25 and 1.0 g/24 h, includ 15 patients (M : F = 9 : 6) with primary glomerulonephritis, mean age 37.87±9.65 years, the mean clearance of endogenous creatinine 82.85±18.48 ml/min, and mean BMI 23.83±1.57 kg/m2. The third group include 15 patients (M : F = 8 : 7) with primary glomerulonephritis, with proteinuria between 1.0 and 3.0 g/24 h, mean age 35.67±13.29 years, the mean clearance of endogenous creatinine 82.85±18.48 ml/min, and mean BMI 23.83±1.57 kg/m2. The fourth group, with proteinuria higher than 3.0 g/24 h, included 15 patients (M : F = 9 : 6) with primary glomerulonephritis, mean age 40.40±9.75 years, the mean clearance of endogenous creatinine 80.16±20.80 ml/min, and mean BMI 24.83±1.44 kg/m2. In order to assess the influence of proteinuria on the lipoprotein (a) metabolism abnormalities we investigated 24-hour proteinuria, the colloid osmotic pressure (COP) of plasma, and the serum concentration of lipoprotein (a). The results were statistically analyzed using ANOVA, Kruscal-Wallis test, Mann-Whitney U test, χ2 test and Spearman test. Results. Statistically, the patients with proteinuria over 3.0 g/24 h had the significantly higher values of lipoprotein (a) in serum as compared to the control group, and the patients with proteinuria about 0.25-1.0 g/24 h. The patients with proteinuria between 1.0-3.0 g/24 h had the statistically significantly higher values of lipoprotein (a) in serum than the control group (proteinuria < 0.25 g/24 h). There was a highly statistically significant negative correlation between serum albumin concentration, COP and the concentration of lipoprotein (a) in serum. There was a highly statistically significant positive correlation between 24-hour proteinuria and the concentration of lipoprotein (a) in serum. Conclusion. Proteinuria leads to the deterioration of lipoprotein (a) abnormalities.